PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU SMK NEGERI 1 KOTA BEKASI - Hotman Napitupulu (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This study aims to analyze influence of organizational motivation and commitment on the performance of SMK Negeri 1 Bekasi teachers, the partial influence of motivation on the performance of SMK Negeri 1 Bekasi teachers. This study uses a quantitative approach. The population in this study is the teacher of SMK Negeri 1 Bekasi City. The sampling technique uses saturated sampling with a sample size of 100 teachers. Data collection techniques using a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression. The results of this study indicate that simultaneous organizational motivation and commitment has a positive and significant effect on the performance of teachers of SMK Negeri 1 Bekasi. Partially, motivation has a positive and significant effect on the performance of teachers of SMK Negeri 1 Bekasi. Partially organizational commitment has a positive and significant effect on the performance of teachers of SMK Negeri 1 Bekasi.